A Review of Adropin as the Medium of Dialogue between Energy Regulation and Immune Regulation. (4th March 2020) - Zhang, Shuyu; Chen, Qingquan; Lin, Xuchen; Chen, Min; Liu, Qicai
Abstract : Adropin is a secretory protein encoded by the energy balance gene and is closely associated with regulation of energy metabolism and insulin resistance. The clinical findings demonstrated its decreased expression in various inflammatory diseases, its negative correlation with the expression levels of inflammatory cytokines, and its potential anti-inflammatory effects. We speculate that adropin plays a pivotal regulatory role in immune cells and inflammatory factors. In this study, we reviewed the advances in researches concentrated on immunological effects of adropin.